An Unknown Correlation in Hexametric Poetry and the Interpretation of the Brevis in Longo Principle - Abritta, Alejandro (Classica - Revista Brasileira de Estudos Clássicos, 2017)
The goal of this paper is to show that (some) Ancient Greek hexametric poets were not indifferent to the quantity of the final syllable of the verse, by studying the correlation between that quantity and the different possible word ends in the fourth foot of the verse. The results of the study suggest that in some poets there was a certain preference for “rhythmic coherence” within the second colon, which indicates that, even if there was “compositional indifference” regarding the quantity of the last syllable, there was not “actual indifference”.